The Role and Importance of the Subject Specialist in the Pac-12 Conference University Libraries - Love, April M.; Mirfakhrai, Mohammad (Journal of library administration, 2021)
This unique study of subject specialists in the academic libraries of the Pac-12 conference universities may be long overdue. The strength of the investigation is a focused sample size and unique inferential statistical analysis of a survey of subject specialists. Pac-12 libraries vary widely with respect to the system's combination of public and private universities, and those who hire candidates with only the Master of Library and Information Science (MLIS) and an additional advanced subject degree. This investigation has the possibility of promoting greater awareness for future roles in which subject specialists may participate and create innovative solutions within academic libraries.